The equation relating distance, d, to time, t, is given by d = 55t, where 55 is the constant of variation. Sarah can travel 330 miles in 6 hours by substituting t = 6 into the equation d = 55t.
The equation that relates the distance, d, to the time, t, when they vary directly is:
d = k * t
where k represents the constant of variation.
To find the value of k, we can use the given information. Sarah travels 440 miles in 8 hours. Substituting these values into the equation:
440 = k * 8
Dividing both sides by 8:
k = 440 / 8
k = 55
Therefore, the equation that relates the distance, d, to the time, t, is:
d = 55t
To find how many miles Sarah can travel in 6 hours, we substitute t = 6 into the equation:
d = 55 * 6
d = 330
Therefore, Sarah can travel 330 miles in 6 hours.
To know more about equation:
#SPJ2
Answer:
d=55t Sara travels 330 miles
Step-by-step explanation:
We are given that distance, d, Sarah drives varies directly to the time, t. This means
d=k⋅t
for some constant, k. Since Sarah travels 440 miles in 8 hours, we substitute these values into the formula for direct variation to find
440=k⋅8
Dividing by 8 gives k=55, so an equation that relates d and t is
d=55t
Substituting t=6 yields
55(6)=330
So Sarah can travel 330 miles in 6 hours.
Answer:19 days because there are 7 days in a week and 7+7=14 and 14+7=19
Step-by-step explanation:
There are 7 days in a week so there is 14 days in 2 weeks.
2 weeks and 5 days is the same as 14 days + 5 days, or C) 19 days
Answer:
The distance between them changing after 10 minutes will be 9.553 mph.
Step-by-step explanation:
The paths of two runners cross at a stop sign (O). One runner is heading south at a constant rate of 6.5 miles per hour towards A while the other runner is heading west at a constant rate of 7 miles per hour towards B.
So, after 10 minutes the first runner covers a distance of miles and the second runner covers a distance of miles.
Therefore, after 10 minutes their distance will be miles.
Now, the distance between them is given by
AB² = OA² + OB²
Now, differentiating this equation with respect to time t (in hours) we get
⇒
⇒
⇒ mph.
Therefore, the distance between them changing after 10 minutes will be 9.553 mph. (Answer)
The distance between the two runners is not changing after 10 minutes.
To find the rate of change of the distance between the two runners, we can use the concept of relative velocity. The distance is changing due to the motion of both runners, so we need to find the rate at which each runner is approaching or moving away from the other. Since one runner is heading south and the other is heading west, their velocities are perpendicular to each other. We can use the Pythagorean theorem to find their combined velocity and then calculate the rate of change of the distance between them.
Let's consider the southward runner as Runner A and the westward runner as Runner B. The velocity of A is 6.5 miles per hour, and the velocity of B is 7 miles per hour. After 10 minutes, the distance traveled by A can be calculated as (6.5 miles/hour) * (10/60) hours = 1.083 miles. The distance traveled by B can be calculated as (7 miles/hour) * (10/60) hours = 1.167 miles.
Using the Pythagorean theorem, we can calculate the distance between the two runners after 10 minutes:
Distance = sqrt((1.083 miles)^2 + (1.167 miles)^2) ≈ 1.563 miles
To find the rate of change of the distance between them, we can differentiate the equation for the distance with respect to time:
d(Distance)/dt = (1/2)*((2*(1.083 miles)*(0))/(sqrt((1.083 miles)^2 + (1.167 miles)^2))) + (1/2)*((2*(1.167 miles)*(0))/(sqrt((1.083 miles)^2 + (1.167 miles)^2))) = 0
Therefore, the distance between the two runners is not changing after 10 minutes.
#SPJ3
The slope of the line that passes through the points (5,10) and (2,12) is
Answer:
m = -2/3; b = 13 1/3
Step-by-step explanation:
ΔX = 2 – 5 = -3
ΔY = 12 – 10 = 2
2/-3 = -2/3
Equation for b:
Answer:
-2/3
Step-by-step explanation:
To find the slope, you use rise over run. so 12 - 10 over 2 - 5. That is 2 over negative 3. so negative two thirds. I hope this helps and please mark me brainliest!
Answer:
Step-by-step explanation:
taking like terms together
taking LCM
taking LCM
splitting the term
splitting the term
we know that
putting this value in above equation